Be Friendly, Never Friend - Quality of Relationship Between Juvenile and Educator - Marcin Jurczyk (Vasyl Stefanyk Precarpathian National University, 2023)
The educator profession at the Youth Detention Centre undoubtedly requires specific abilities, skills, and concrete knowledge since, from the beginning of their work, an educator must interact with youth who often exemplify pathological behaviour models. The article refers to the paradigms of social rehabilitation pedagogy. Referring to the social rehabilitation process of minors, it is worth presenting the figure of a social rehabilitation educator, who undoubtedly plays a vital role in this process. The role of an educator, perceived as a helping person, is not the easiest one, especially when working with demoralized people who do not comply with social and legal norms. The staff must have a positive attitude towards social rehabilitation goals. The article's primary purpose is a contemporary reflection on understanding the art of being an educator, a social rehabilitation pedagogue, communication, the relationship between the educator and the juvenile, and the barriers in everyday work with juveniles at social rehabilitation centres. As an autotelic value, juveniles staying in social rehabilitation institutions deserve subjective and understanding relationships with an educator whose competencies, desire for personal development, and knowledge of their weaknesses will contribute to creating an interaction initiating the juvenile's moral transformation process.